ADVANTAGES OF DUAL EDUCATION IN TRAINING QUALIFIED ENGINEERING PERSONNEL IN TECHNICAL HIGHER EDUCATION INSTITUTIONS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The article talks about the features and advantages of dual education, which allows solving the problem of professional training in the preparation of qualified engineering and technical personnel in technical universities.